1988
DOI: 10.1111/j.1463-6395.1988.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of Vanadium, Sulphur and Bromine Within the Vanadocytes of Ascidia mentula Müller: A Quantitative Electron Probe X‐Ray Microanalytical Study

Abstract: Levels of vanadium, sulphur and bromine within the vanadopohores of Ascidia mentula vanadocytes have been determined by quantitative X‐ray microanalytical techniques. Values obtained for vanadophore vanadium in thin sections correspond to 2.5‐3.25% or 0.5‐0.65 molal aqueous solutions in vivo. Quantitation of sulphur in thin sections gives levels an order of magnitude lower than for vanadium, but it is likely that major losses of sulphur have occurred, since analysis of unfixed, air dried vanadocytes gives V/S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…bryozoans (Walls et al, 1991, Anthoni et al 1990), molluscs (Williams et al 1986, Kernan et al 1988, Faulkner et al 1990, Avila et al 1990, Di Marzo et al 1991, polychaetes (Fielman 1989, Goerke & Weber 1990. echinoderms (Lucas et al 1979) and tunicates Resale of full artide not permitted (Lane & Wilkes 1988, Lindquist et al 1992, has demonstrated that substantial chemical variation occurs over a range of spatial scales, including within organisms (llIIl to em), among organisms (cm to m), and over geographic areas (1 to 10 3 km). In contrast, temporal variation of secondary metabolites among marine invertebrate species has not been as well studied, although some temporal variation appears to be asso· dated with spawning activity or other discrete events (Sammarco & Coll 1988, Coll et al 1989, Green et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…bryozoans (Walls et al, 1991, Anthoni et al 1990), molluscs (Williams et al 1986, Kernan et al 1988, Faulkner et al 1990, Avila et al 1990, Di Marzo et al 1991, polychaetes (Fielman 1989, Goerke & Weber 1990. echinoderms (Lucas et al 1979) and tunicates Resale of full artide not permitted (Lane & Wilkes 1988, Lindquist et al 1992, has demonstrated that substantial chemical variation occurs over a range of spatial scales, including within organisms (llIIl to em), among organisms (cm to m), and over geographic areas (1 to 10 3 km). In contrast, temporal variation of secondary metabolites among marine invertebrate species has not been as well studied, although some temporal variation appears to be asso· dated with spawning activity or other discrete events (Sammarco & Coll 1988, Coll et al 1989, Green et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…C1 and K were found in most blood cells of Phallusia mammillata as can be seen in Table 1. These elements were not found in cells after chemical fixation (Rowley, 1982;Lane and Wilkes, 1988). Only Pirie and Bell (1984) reported on traces of C1 in some cells of Ascidia mentula and Ascidiella aspersa blood.…”
Section: Discussionmentioning
confidence: 90%
“…A considerable amount of sulfate is always associated with the vanadium in ascidian blood cells (Henze, 1932;Califano and Boeri, 1950;Bielig et al, 1954;Levine, 1961;Botte et al, 1979a,b;Scippa et al, 1982Scippa et al, , 1985Scippa et al, , 1988Bell et al, 1982;Pirie and Bell, 1984;Lane and Wilkes, 1988;Frank et al, 1986Frank et al, , 1987Frank et al, , 1994Frank et al, , 1995Anderson and Swinehart, 1991). This suggests that sulfate might participate in the accumulation and reduction of vanadium or play an unknown biological role.…”
Section: Sulfate In Vanadocytesmentioning
confidence: 92%